Influence of concrete mix properties on technology of arrangement column foundations - Tonkacheev, G.; Nosach, K. (Ways to Improve Construction Efficiency, 2020)
The article analyzes the selection of concrete mix for the device of the columnar foundation under the column of the frame structure. Depending on the technology of the device - monolithic, prefabricated, prefabricated-monolithic - the main factors influencing the choice are determined. Frame structures have been actively erected since the beginning of the 20th century, with the development of industrial construction. The advantages of frame structures are the unification of structural elements, the possibility of using prefabricated elements, universal planning of the structure, its durability. According to the purpose of the building can be warehouse, factory and retail space. At construction of a frame construction there is a question not only in a choice of technology of the device of these or those elements, but also selection of materials, in particular concrete mix. When installing frame structures often use ready-made structural elements of precast concrete or metal. This reduces the duration of construction, and, accordingly, reduce labor costs and operating time of mechanisms. When using prefabricated elements, the weather influence on the course of construction works is practically leveled. Reinforced concrete and metal structures made in the factory, as a rule, meet the required quality characteristics. As for the technology of laying foundations, in particular columnar, the question often arises about their construction in a rational way. The cost of prefabricated foundation structures is higher than monolithic ones due to factory, loading and unloading and transport costs. However, with this technology the foundations are installed in a short time. The technology of installation of monolithic foundations depends on weather conditions, is characterized by high labor costs and the duration of the process loses to the prefabricated method. In the conditions of water-saturated soils monolithic concreting is complicated, as it is necessary to take measures for drainage [1]. There is also a prefabricated monolithic technology of foundations, which allows the rational use of both technologies. For example, to reduce the time and reduce the complexity, you can arrange a monolithic foundation with a prefabricated glass, or, if there is water in the pit, you can use a prefabricated foundation slab and a monolithic glass with a formwork retainer module [1]. The construction of columnar foundations differs in the volume of concrete depending on the load and soil conditions. Sometimes the volume of concrete reaches tens of cubic meters per foundation, so the problem of taking into account the properties of the concrete mixture becomes relevant. First of all, there are questions about the selection of the composition of the concrete mixture and the technology of its delivery to the site. The influence of the properties of the concrete mixture is considered by example. For example, the following properties of the concrete mixture were taken into account: ease of laying, which depends on the complexity of laying the concrete mixture; expediency of use of the special chemical additives improving some properties of concrete mix; the maximum allowable size of the fraction; rigidity of concrete mix; compaction. The results are shown in the table, which clearly shows the difference in the required volume.